Left atrial volume changes during exercise stress echocardiography in heart failure and hypertrophic cardiomyopathy. (14th October 2021) - Wierzbowska-Drabik, K; Ciampi, Q; Peteiro, J; Re, F; D'Alfonso, M.G; Agoston, G; Varga, A; Djordjevic-Dikic, A; Tesic, M; Rodriguez-Zanella, H; Simova, I; Merli, E; et al.
Abstract: Background: Left atrial volume (LAV) may dilate acutely during exercise stress echocardiography (ESE) in chronic coronary syndromes. Purpose: To assess the feasibility and functional correlates of LAV during ESE outside coronary artery disease. Methods: We performed ESE (semi-supine bike in 159 or treadmill in 105 patients) in 264 patients (155 male, age 58±15 years) with heart failure with preserved ejection fraction (HFpEF, n=82), heart failure with reduced ejection fraction (HFrEF, n=51) or hypertrophic cardiomyopathy (HCM, n=131). LAV was measured with the biplane disk summation method. LAV-dilators were defined as those with stress-rest increase in LAV index ≥6.8 ml/m 2, a cutoff derived from a calculated reference change value above the biological, analytical and observer variability of LAV. Average E/e', mitral regurgitation (MR, graded from 0 = absent to 3 = severe), left ventricular ejection fraction, systolic pulmonary arterial pressure (SPAP) from tricuspid regurgitant jet velocity and B-lines (4-sites simplified scan) were also measured. Results: Measurement success rate was 264/264 (100%) in technically adequate images. At group analysis LAV changes during ESE were heterogeneous, with LAV index increase in HFrEF (rest = 41±26 vs stress = 44±27 ml/m 2, p=0.563) and HCM (rest = 39±18 vs stress = 41±17 ml/m 2, p=0.444) and mild decrease in HFpEF (rest= 28±12 vs stress = 26±11 ml/m 2, p=0.020). At individual patient analysis, LAV dilation occurred in 88 (33%) patients: 9 with HFpEF (11%), 24 with HFrEF (47%), 55 with HCM (42%, p<0.001 vs HFpEF). Prevalence of LAV dilation was 33/105 with treadmill and 55/159 with semi-supine ESE (31 vs 35%, p=0.588). In the overall population, LAV stress-rest change was directly related to stress SPAP (r=0.264, p=0.001), peak E/e'(r=0.288, p<0.001), stress B-lines (r=0.223, p=0.003) and peak MR grade (r=0.295, p<0.0001). LAV-dilators more frequently showed abnormal values of SPAP, B-lines, MR and E/e'during ESE compared to non-dilators (see figure). Conclusion: LAV assessment during ESE is feasible with high success rate, and LAV dilation is equally frequent with upright treadmill or semi-supine bike exercise. LAV individual response to stress is unpredictable, with a significant dilation occurring more frequently in HCM and HFrEF compared to HFpEF patients. Across all conditions, LAV dilation is correlated to more advanced pulmonary and hemodynamic congestion, higher left ventricular filling pressures and more severe MR during stress. Funding Acknowledgement: Type of funding sources: None.